Prophylactic penicillin after 5 years of age in patients with sickle cell disease: A survey of sickle cell disease experts1. Issue 6 (28th November 2012) - McCavit, Timothy L.; Gilbert, Megan; Buchanan, George R.
Abstract Background Since the publication of the Prophlyactic Penicillin Study II in 1995, the management of penicillin prophylaxis for children with sickle cell disease (SCD) after 5 years of age has been controversial. In this study, we sought to describe current practice patterns of pediatric hematologists related to cessation of penicillin prophylaxis for children with SCD after 5 years of age. Procedure We performed a cross‐sectional, electronic survey of pediatric hematologists with expertise in SCD to examine practices regarding penicillin prophylaxis in children with SCD after 5 years of age. We also investigated factors potentially associated with continuation of penicillin prophylaxis using the Jonckheere–Terpstra test and Fisher's exact test. Results Of the 106 physicians surveyed from 76 centers, 84% completed the survey. Among respondents, 76% routinely recommended cessation of penicillin prophylaxis after 5 years of age. The practice of routinely continuing penicillin after 5 years of age was associated with decreased concern about antibiotic resistance in Streptococcus pneumoniae (P = 0.01), with the usage of prophylactic penicillin in mild SCD genotypes (sickle hemoglobin‐C disease and sickle β+ thalassemia, P = <0.001), and with increasing use of other preventive evaluations (e.g., MRI for silent stroke) in childhood (P = 0.05). Conclusion Most pediatric hematologists with an SCD expertise recommend cessation of prophylactic penicillin after 5 years of age. Pediatr Blood Cancer 2013; 60: 935–939. © 2012 Wiley Periodicals, Inc.